Essays on environmental and agricultural economics - Lima Filho, Francisco Luis (2020)
This thesis contains three independent but interrelated articles within the field of environmental and agricultural economics. Essentially, I empirically investigate topics related to the impacts of agricultural mechanization and the impacts of agricultural regulations on trade. Below follows a brief description of the three articles. The first paper, written jointly with Francisco J. M. Costa, shows how the adoption of agricultural mechanization can prompt structural transformation in an emerging economy. We study the fast spread of mechanical harvesting that followed the prohibition of pre-harvest field burning in the sugarcane sector in São Paulo state, Brazil. We combine remote-sensing data on sugarcane production and censuses data to estimate the impacts of field mechanization on the local labor markets. We find that the adoption of mechanical harvesting led to the industrialization of the field; one standard deviation larger adoption of agricultural mechanization reduces the share of workers employed in the agricultural sector by 2.3 percentage points, and increases the employment share of manufacturing and services sector by 1.7 and 1.1 percentage points, respectively. The second article, written with Francisco J. M. Costa and Letícia Nunes, studies if and how the adoption of a new agricultural technology that reduces agricultural fires can ameliorate local health outcomes. We investigate the fast spread of mechanical harvesting in the sugarcane sector in São Paulo state, Brazil. We assess two channels through which mechanization could affect health outcomes: a direct reduction in air pollution from field burning, and an indirect effect through income increase. By combining remote-sensing data on the sugarcane production, annual particulate matter data, census information, and official health records, we estimate the impacts of agricultural mechanization on pollution, income per capita, and infant hospitalizations and mortality. Our instrument for the adoption of combine harvesters is the slope of sugarcane fields. Results suggest that the adoption of this new technology did not improve air quality, but increased average household income and reduced infant hospitalization. We also find that this reduction in infant hospitalization was concentrated in the non-harvest season, suggesting that the direct effect of reduced field burning is not the main driver of the health gains. Lastly, the third paper, co-authored with Rafael Ornelas, estimates the effects of a set of non-tariff barriers (NTB) regulations imposed by the European Union (EU) between 1997 and 2002 on trade flows of beef products. We introduce NTB regulations in a trade model a la Melitz (2003) and Chaney (2008) to analyze their impacts on trade flows. Our model predicts that after a group of countries impose a NTB regulation within group trade flows increase if exports from this group to the rest of the world decreases or if this group's imports from the rest of the world increases. We test this prediction empirically using a differences-in-differences approach. We find that EU's regulations on beef products increased trade of beef products between EU countries by 20%, reduced EU exports to non-EU countries by around 40%, and reduced EU imports of the regulated goods from non-EU countries by 60%.